Application of the Rice Method Handling Principles (Rest, Ice, Compression, Elevation) in Minor Sports Injuries (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the extent of understanding and application of the principles of handling minor injuries using the RICE method (Rest, Ice, Compression, Elevation) in individuals who have experienced or handled minor sports injuries. The research method used was a quantitative approach with a descriptive analysis design, which was carried out through distributing questionnaires to 25 respondents. The research instrument consisted of 20 questions that measured the respondents' understanding, attitudes, and constraints in applying the RICE principles. The results showed that the majority of respondents had a good understanding of the RICE principles, with the application of Rest, Ice, and Elevation steps being more dominant than Compression. Some respondents still experienced technical obstacles, such as limited access to elastic bandages and a lack of in-depth understanding of the duration of cold compress use. The level of agreement with the effectiveness of this method is high, with 80% of respondents choosing the answers "Agree" and "Strongly Agree". Based on these findings, it can be concluded that the RICE method is an effective and well-recognized first step in the management of minor injuries, although additional education is needed, especially in the practical aspects of its application. Increased awareness and technical skills in applying these principles are essential to optimize the recovery process and prevent further complications in sports activities.